Design and potentiostat circuit for neurochemical sensing: article / Ahmad Farhan Yahaya - Yahaya, Ahmad Farhan (2009)
This paper presents electrochemical cell that will be applied to potentiostat circuit to show its characteristics. The potentiostat circuit consists of electronic devices and components, including op amp, to set up a control circuit for neurochemical sensing. The circuit is required to go under simulation tools such as PSice, Multisim or Simulink to design and simulate the circuit for analyzing its performance and parameters involved. The voltage source, Vsrc, of the circuit should be same with the voltage cell, Vcell, between reference electrode and working electrode. Output voltage is depending on current flow across electrochemical cell.